Capturing CO2 from an integrated steel mill: a techno-economic analysis through process modelling - Duwahir, Zahras Mohamed (2016)
The increase in global carbon dioxide emission has raised concerns about climate change. This has caused nations to consider different carbon dioxide mitigation pathways to reduce emissions. The iron and steel industry contributes to approximately 30% of total global CO2 direct emission in the industrial sector. It is an energy intense industry. Many steel mills are operating close to thermodynamic limits in efficiency. Therefore decarbonising the steel industry through process improvements is limited. Breakthrough technologies such as carbon capture and storage (CCS) is an alternative and attractive solution.